Answer:
4 minutes left
Step-by-step explanation:
20 - 16 = 4
Answer:
![\frac{(a-b)^2+b^2}{a^2}](https://tex.z-dn.net/?f=%5Cfrac%7B%28a-b%29%5E2%2Bb%5E2%7D%7Ba%5E2%7D)
Step-by-step explanation:
Since, By the given diagram,
The side of the inner square = Distance between the points (0,b) and (a-b,0)
![=\sqrt{(a-b-0)^2+(0-b)^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B%28a-b-0%29%5E2%2B%280-b%29%5E2%7D)
![=\sqrt{(a-b)^2+b^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B%28a-b%29%5E2%2Bb%5E2%7D)
Thus the area of the inner square = (side)²
![=(\sqrt{(a-b)^2+b^2})^2](https://tex.z-dn.net/?f=%3D%28%5Csqrt%7B%28a-b%29%5E2%2Bb%5E2%7D%29%5E2)
![=(a-b)^2+b^2\text{ square cm}](https://tex.z-dn.net/?f=%3D%28a-b%29%5E2%2Bb%5E2%5Ctext%7B%20square%20cm%7D)
Now, the side of the outer square = Distance between the points (0,0) and (a,0),
![=\sqrt{(a-0)^2+0^2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B%28a-0%29%5E2%2B0%5E2%7D)
![=\sqrt{a^2}=a](https://tex.z-dn.net/?f=%3D%5Csqrt%7Ba%5E2%7D%3Da)
Thus, the area of the outer square = (side)²
![=a^2\text{ square cm}](https://tex.z-dn.net/?f=%3Da%5E2%5Ctext%7B%20square%20cm%7D)
Hence, the ratio of the area of the inner square to the area of the outer square
![=\frac{(a-b)^2+b^2}{a^2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%28a-b%29%5E2%2Bb%5E2%7D%7Ba%5E2%7D)
Answer:
No, the student's work is not correct.
Step-by-step explanation:
Given : Student expanded an expression, as shown.
![-6(4x-\frac{2}{13} )](https://tex.z-dn.net/?f=-6%284x-%5Cfrac%7B2%7D%7B13%7D%20%29)
![-6(4x)+6(-\frac{2}{13} )](https://tex.z-dn.net/?f=-6%284x%29%2B6%28-%5Cfrac%7B2%7D%7B13%7D%20%29)
![-24x-\frac{12}{13}](https://tex.z-dn.net/?f=-24x-%5Cfrac%7B12%7D%7B13%7D)
To find : Is the student's work correct?
Solution :
The expansion of student is not correct.
Follow the below steps to get correct solution and student mistake,
Step 1 - Write the expression,
![-6(4x-\frac{2}{13} )](https://tex.z-dn.net/?f=-6%284x-%5Cfrac%7B2%7D%7B13%7D%20%29)
Step 2 - Apply distributive property, ![a(b+c)=ab+ac](https://tex.z-dn.net/?f=a%28b%2Bc%29%3Dab%2Bac)
![=(-6)(4x)+(-6)(-\frac{2}{13})](https://tex.z-dn.net/?f=%3D%28-6%29%284x%29%2B%28-6%29%28-%5Cfrac%7B2%7D%7B13%7D%29)
Step 3 - Solve,
![=-24x+\frac{12}{13}](https://tex.z-dn.net/?f=%3D-24x%2B%5Cfrac%7B12%7D%7B13%7D)
The student was mistaken in step 2 in solving the sign.
The formula is y = mx + b when b = y-intercept and m is the slope.
Slope = Rise/Run So 1/2.
Y-Int. = The y value at which x = 0. Which is -3
The line has the formula:
Y = 1/2x - 3
Hope this helps :)
Answer:
Step-by-step explanation:
1 yes 2 no 3 no 4 yes 5 no